Influence of the skier´s body geometry on the duration of the giant slalom turn - Hraski, Z.; Hraski, M. (Science and Skiing IV, 2009)
INTRODUCTION: The basic aim of every skier is to execute each turn, from start to finish, as fast as possible. To accomplished that it is essential for each turn to be executed technically perfect, because even the smallest error will have an impact on the loss of the speed, therefore affecting the overall time. The aim of this investigation was to determine the differences in body geometry of a skier related to the duration of the giant slalom turn.